The Reagan Administration as the Origin of the Shift from Citizen to Consumer Building in American Education - Davis, Alexander (Université d'Ottawa / University of Ottawa, 2017)
Current American education is comprised of and influenced by a myriad of complex legislative, technological, and cultural representations of consumption, however this historic-educational study specifically examines how the Reagan administration discursively initiated the consumerizing educational framework. While existing research studies the neoliberal implications on education, this study addresses the neoliberal reforms under President Reagan within the discursive paradigm of its consumerizing impact. By using Critical Discourse Analysis on a selection of Presidential proclamations, speeches, and national educational reports, this study examines and elucidates how the Reagan administration created the consumerizing framework for American education. The Reagan administration distinguished American education from its predecessors as prioritizing the consuming potential of students, while simultaneously situating education as a commodity. The Reagan administration discursively positioned education as a commodity by implementing the free market values of competition and choice. Through Reagan’s encouragement of corporate involvement and rewarding the tenacity of business initiatives in education, American education transitioned from a democratic ideal to a market-oriented institution. This was specifically accomplished through positioning Reagan’s predecessors as misguided and situating Reagan as a rescuer, while legitimating the reforms as adhering to the American spirit. Similarly, business was presented as embodying the essence of the American spirit and being a rejuvenating force. Choice and competition were recontextualized from their economic purpose and recommended as a new form of educational governance. By understanding the results through the lens of some Frankfurt School thinkers and expanding on Bowles and Gintis’ educational theory, this study argues that Reagan’s reforms embodied a physical consumerizing aspect and an interactional consumerizing facet as necessary for the economy of post-industrial America.
Keywords: Education; Consumerism; Neoliberalism; Critical discourse analysis